La opinión de los españoles sobre Felipe V después de la Guerra de Sucesión - García Cárcel, Ricardo (Cuadernos de Historia Moderna, 2002)
The author analyses the opinion about Philip y from 1714 to 1746. It put in evidence the echo that the bourbon repression in the opinion of Crown of Aragon in the following years to the War. After 1725 it emphasizes the paradoxical lack of syntony of chronicles of the War with Philip V, the limitations of the power of the own king that are reflected in the dialectic with the intellectuals of the moment, and the strange lack of praises to king Philip V during its reign until its death that only provokes few gloss obituary like the Epitome.